2018
DOI: 10.1186/s12872-018-0825-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident atrial fibrillation in patients presenting with retinal artery or vein occlusion: a nationwide cohort study

Abstract: BackgroundThe inter-relationships of atrial fibrillation (AF) to retinal vascular occlusions (whether retinal artery occlusion (RAO) or retinal venous occlusion (RVO)) remain unclear. It is unknown if a presentation of retinal artery or venous occlusions may indicate a new onset cardiac arrhythmia. To shed light on this association, we investigated the risk of new onset AF in patients with known RAO and RVO.MethodsPatients with retinal occlusions from 1997 to 2011 were identified through Danish nationwide regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Previous studies from Hayreh et al [ 21 ] and Yen et al [ 19 ] draw a potential pathophysiologic association, as they have reported that patients with AF are at increased risk of developing RAO. A study by Christiansen et al [ 22 ] also found that RAO was associated with an increased risk of incident AF. O'Mahoney et al [ 23 ] and Christiansen et al [ 24 ] reported that RVO might be an important cause of blindness in populations with high atherosclerotic risk.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies from Hayreh et al [ 21 ] and Yen et al [ 19 ] draw a potential pathophysiologic association, as they have reported that patients with AF are at increased risk of developing RAO. A study by Christiansen et al [ 22 ] also found that RAO was associated with an increased risk of incident AF. O'Mahoney et al [ 23 ] and Christiansen et al [ 24 ] reported that RVO might be an important cause of blindness in populations with high atherosclerotic risk.…”
Section: Discussionmentioning
confidence: 95%
“…Data from previous studies support the use of long‐term monitoring for detection of atrial fibrillation as short‐term ECG monitoring of 1 day to 1 month is less effective 11,12,14 . There are limited data on the association of atrial fibrillation and CRAO 5,15–17 . Previous studies have advocated cardiac monitoring for as little as 24 hours to as long as 1 month post‐CRAO.…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies concerning the relationship between RAO and AF indicate that there is a correlation between AF and RAO. RAO episodes were more frequently observed in the AF group, and RAO patients were more frequently diagnosed with AF compared with control groups [9][10][11][12]. A higher rate of rehospitalization of RAO patients compared with ischemic stroke patients due to cardiac arrhythmias including AF is also noteworthy, indicating the necessity to conduct a mandatory diagnostic evaluation in this group of patients for AF [16], especially given the fact that RAO patients are at a high risk of stroke in the period immediately following RAO [6,[16][17][18][19][20].…”
Section: Atrial Fibrillation As One Of the Causes Of Raomentioning
confidence: 98%
“…Most commonly, RAO is a consequence of an embolism originating from atherosclerotic plaques in the ipsilateral carotid artery, heart, or aortic arch [4,8]. Recently, the role of cardiac arrhythmias in the aetiology of RAO has also been receiving increasing attention [9][10][11][12][13][14][15][16]. Results of previous studies concerning the relationship between RAO and AF indicate that there is a correlation between AF and RAO.…”
Section: Atrial Fibrillation As One Of the Causes Of Raomentioning
confidence: 99%
See 1 more Smart Citation